2020
DOI: 10.3390/biomedicines8120637
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and p53: Dual Target for Cancer Therapy

Abstract: The tumor suppressor p53 is considered the “guardian of the genome” that can protect cells against cancer by inducing cell cycle arrest followed by cell death. However, STAT3 is constitutively activated in several human cancers and plays crucial roles in promoting cancer cell proliferation and survival. Hence, STAT3 and p53 have opposing roles in cellular pathway regulation, as activation of STAT3 upregulates the survival pathway, whereas p53 triggers the apoptotic pathway. Constitutive activation of STAT3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 198 publications
1
28
0
Order By: Relevance
“…STAT3 inactivation is also associated with ferroptosis. It has been reported that STAT3 inhibits P53 to facilitate tumour progression by binding to the promoter of p53, which is an important regulator of ferroptoss [ 21 , 48 ]. Qiang et al found that increasing the expression of p-STAT3 could alleviate ferroptosis via SLC7A11 in MLE12 cells by regulating SLC7A11 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 inactivation is also associated with ferroptosis. It has been reported that STAT3 inhibits P53 to facilitate tumour progression by binding to the promoter of p53, which is an important regulator of ferroptoss [ 21 , 48 ]. Qiang et al found that increasing the expression of p-STAT3 could alleviate ferroptosis via SLC7A11 in MLE12 cells by regulating SLC7A11 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription 3 (STAT3) belongs to the STAT family and is a vital transcription factor involved in inflammation and tumour progression [ 20 ]. Classical STAT3 activation involves the phosphorylation of STAT3 at Tyr705 (p-STAT3 (705)), which interacts with and inhibits P53 [ 21 ]. Wang et al discovered that high expression of STAT3 is relevant to increased malignancy and poor prognosis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…P53 is one of tumor suppressor genes that most widely studied in human cancer, and the activation of p53 mainly leads to the inhibition of cancer cells growth and promotes DNA repair and apoptosis, the role is mainly mediated by its transcriptional activity. In tumor cells, accompanied by the activation of the IL-6/STAT3 signaling pathway, phosphorylated STAT3 can bind to the promoter of the p53 gene to inhibit its transcription, thereby blocking the inhibitory effect of p53 on oncogene transcription ( 61 ). Alpha-fetoprotein (AFP) is a single-stranded serum glycoprotein, an important biomarker commonly used in the clinical diagnosis of HCC, it is a specific protein with high expression during the occurrence of liver cancer.…”
Section: The Role Of the Il-6/stat3 Signaling Pathway In The Initiation Of Liver Cancermentioning
confidence: 99%
“…STAT3 is a downstream effector of ALK that plays an important role in promoting cell survival, proliferation, and immune evasion (11). STAT3 exerts anti-apoptotic effects in ALK+ ALCL mainly by upregulating the anti-apoptotic protein B cell lymphoma extra-large (Bcl-xL) and antagonizing the tumor suppressor P53 (12). STAT3-induced expression of transforming growth factor (TGF)-b, interleukin (IL)-10, and programmed death ligand (PD-L1,CD274, B7-H1) creates a tumor-suppressive microenvironment (13)(14)(15).…”
Section: Signaling Pathways In Alk+ Alcl 21 Stat3 Pathwaymentioning
confidence: 99%